The role of pedunculopontine nucleus in isolated REM sleep behavior disorder and REM sleep without atonia - Aygün, Demet; Ertaş, F. İnci; Gündüz, Ayşegül; Benbir Şenel, Gülçin; Karadeniz, Derya; Kızıltan, Meral (Parkinsonism & related disorders, 2021)
The aim of this study was to analyze the functions of pedunculopontine nucleus (PPN) in isolated REM sleep behavior disorder (iRBD) and REM sleep without atonia (RSWA) to investigate the role of PPN in dream-enacting motor behaviors in RBD. We evaluated the activity of PPN through the prepulse modulation (PPM) together with other brainstem reflexes to investigate the differences in changes at brainstem. We included nine patients with isolated RSWA and 10 patients with iRBD. For diagnosis, all patients underwent polysomnography. None of the patients had parkinsonism or dementia. We also included 17 healthy participants with similar age and sex. Blink reflex (BR), PPM of BR, recovery excitability of BR, and auditory startle reflex (ASR) were recorded in all participants. There was a prepulse inhibition deficit in iRBD and RSWA groups compared to healthy subjects. The BR-R2 recovery at 200 ms interval was also higher in patients with iRBD and RSWA. In ASR recordings, the response probabilities were higher in the RBD group compared to RSWA and control groups. The PPM was abnormal in both iRBD and RSWA whereas ASR was enhanced in iRBD. We suggest that there are certain similarities and differences in the pathophysiologies of iRBD and RSWA. •In isolated REM behavior disorder, there is abnormal prepulse modulation and auditory startle reflex.•In isolated REM sleep without atonia, there is abnormal prepulse modulation.•There is also earlier R2 recovery excitability in both groups.